Diagnosis Of Nickel Industry Downstreaming Policy In Export Restriction Towards Increasing Economic Added Value In Indonesia - Farawansa, Syukron Mahal; Gultom, Elfrida Ratnawati (JURNAL LEGALITAS, 2024)
The phrase â€œcontrol nickel, control the worldâ€ is often used when discussing Indonesia's critical role in the global nickel market. In January 2020, President Jokowi's administration temporarily banned nickel ore exports, as outlined in the Minister of Energy and Mineral Resources Regulation Number 11 of 2019. This study aims to diagnose whether the downstream policy of the nickel mining industry can provide an increase in economic added value in Indonesia The type of research used by the author is normative legal research. Results, The export ban is not intended to hamper trade, but to utilize nickel resources for the country's prosperity through the domestic processing chain. The nickel ore export ban is intended to meet the raw material needs of Indonesian smelters. The ban policy cannot be delayed because mineral resources, especially nickel, are exhausted and non-renewable. With the enactment of Minister of Energy and Mineral Resources Regulation No. 11/2019, there are contradictions in its implementation, especially for foreign investors. This is because the selling price of nickel from Indonesia will automatically be higher than before. However, the implementation of this regulation will not only affect the pace of investment in Indonesia. The Indonesian government has also opened the possibility by offering ease of licensing as mentioned above. Currently, Indonesia needs funds for the construction of smelters (refineries), the construction of its power plants which are the main drivers of nickel processing machines, as well as the training of experts and human resources to do nickel processing properly. Of course, you need a lot of money. In order to accelerate the economy and development, the government has the right to mandate all Indonesian mining companies to prohibit the processing of mining products and the export of raw materials, boost international market prices and boost foreign exchange through increased mining. take action. New renewable energy of the future.